IDENTIFIKASI LONGSORAN LERENG DI RUAS BAMBANGAN – AJI KUNING KALIMANTAN TIMUR KM 6+500 & PENANGANAN MENGGUNAKAN DINDING PENAHAN TANAH - Rusliansyah Rusliansyah; Aulia Isramaulana; Yunizar Antoni Akbar (INFO-TEKNIK, 2013)
This paper discusses the handling of slope sliding occured in the segment of Bambangan – Aji kuning East Borneo. The slide occurs because of unprotected slopes and soil types in the form of silt sandy. Treatment methods cantilever retaining walls was designed inorder to handle the sliding. The cost of the this method was also calculated to obtain the price.Soil investigation and topography data were collected as a secondary data. The design was commenced by preliminary design for this method. The next step was continued with the calculation of safety factor of sliding, overtuning, and bearing capacity. For cantilever, the design was included the calculation of reinforcement. Overal stability of slope was performed using Plaxis Professional 8.2. The cost analysis was performed using Bina marga 2010 method.By using the cantilever, the dimension of the pedestal are 3m wide, 0.5 m thick matsand wall and 5m high. the safety factor of overal stability for both method was higher than that of caltilever wall.. The cost of the reinforcement using cantilever Rp 489.373.268,.